2011
DOI: 10.1016/j.humpath.2010.05.026
|View full text |Cite
|
Sign up to set email alerts
|

TMPRSS2-ERG gene fusion in small cell carcinoma of the prostate☆

Abstract: Recent studies have shown that most prostate cancers carry the TMPRSS2-ERG gene fusion. Here we evaluated the TMPRSS2-ERG gene fusion in small cell carcinoma (SCC) of the prostate (n=12) in comparison with SCC of the urinary bladder (n=12) and lung (n=11). Florescence in situ hybridization demonstrated rearrangement of the ERG gene in 8 cases of prostatic SCC (67%), and the rearrangement was associated with deletion of the 5' ERG gene in 7 cases. But rearrangement of the ERG gene was not present in any SCC of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(54 citation statements)
references
References 27 publications
2
52
0
Order By: Relevance
“…ERG gene rearrangements (primarily deletions) have been reported as a marker specific to carcinomas of the prostate, and a high concordance was found in the small cell and malignant acinar component in patients with tumors displaying dual differentiation [17,18,19,20]. This finding supports a common derivation for these two types of prostatic carcinoma.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…ERG gene rearrangements (primarily deletions) have been reported as a marker specific to carcinomas of the prostate, and a high concordance was found in the small cell and malignant acinar component in patients with tumors displaying dual differentiation [17,18,19,20]. This finding supports a common derivation for these two types of prostatic carcinoma.…”
Section: Discussionsupporting
confidence: 57%
“…A significant development in the characterization of both prostatic PA and SCC was the identification of gene fusions between the ETS-related gene, ERG , and a transmembrane protease, serine 2 (TMPRSS2) , both located on the long arm of chromosome 21 [17]. ERG gene rearrangements (primarily deletions) have been reported as a marker specific to carcinomas of the prostate, and a high concordance was found in the small cell and malignant acinar component in patients with tumors displaying dual differentiation [17,18,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Dual immunohistochemistry for AR and CHGA on the same patient's diagnostic biopsy (prior to NHT; diagnosis of adenocarcinoma, Gleason 4 + 5) revealed that biopsy contained few CHGA positive cells, while the prostatectomy sample (after 8 months of goserelin and flutamide) harbored few AR positive foci ( Figure 1H, Additional file 2: Figure S2). Although we cannot exclude biopsy sampling bias, FISH on the prostatectomy sample confirmed the presence of the androgen-driven TMPRSS2-ERG rearrangement, suggesting an adenocarcinoma origin for the NEPC component within tumor T20 and the potential that this therapy resistant tumor was driven (at least in part) by NHT treatment (Figure 1; Additional file 2: Figure S2; Additional file 3: Text S1) [14][15][16][17].…”
Section: Evidence Of Therapy Response and Resistance In Neoadjuvant Tmentioning
confidence: 91%
“…It is difficult to distinguish prostate small cell carcinoma from bladder small cell carcinoma especially in small biopsy samples. Four independent studies showed that the frequency of ERG alterations in prostate small cell carcinoma is the same as in adenocarcinoma [95][96][97][98] . Thus, ERG rearrangement was found in approximately half of tested prostate small cell carcinoma samples, but was not detected in small cell carcinoma of another origin (for example bladder small cell carcinoma or lung small cell carcinoma).…”
Section: Discussionmentioning
confidence: 99%